Effect of Group Impromptu Music Therapy on Emotional Regulation and Depressive Symptoms of College Students: A Randomized Controlled Study - Zhang, Ming; Ding, Yi; Zhang, Jing; Jiang, Xuefeng; Xu, Nannan; Zhang, Lei; Yu, Wenjie (Frontiers in Psychology, 2022)
Difficulty in emotional regulation is significantly correlated with depression. Depression is a psychological disease that seriously affects the physical and mental health of college students. Therefore, it is of great importance to develop diversified preventive interventions such as group impromptu music therapy (GIMT). The main purpose of this study was to evaluate the effect of GIMT on the improvement of emotional regulation ability and the reduction of depressive symptoms in college students. 71 college students (36 in the experimental group and 35 in the control group) were recruited to carry out randomized controlled trial was used. The experimental group was intervened by GIMT. After the 4th week of intervention, follow-up and scale measurement were carried out. In the experimental group, emotional regulation difficulty scales (DERS) showed significant difference before and after GIMT, implying the improvement in the emotional regulation. But there was no significant improvement in the control group. In addition, the depressive symptoms of experimental group were relieved. All findings showed that GIMT can effectively improve college students' emotional regulation and reduce depressive symptoms.